2011
DOI: 10.4061/2011/219706
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis-Associated Stroke in Children and Youth

Abstract: Diabetic ketoacidosis (DKA) is a state of severe insulin deficiency, either absolute or relative, resulting in hyperglycemia and ketonemia. Although possibly underappreciated, up to 10% of cases of intracerebral complications associated with an episode of DKA, and/or its treatment, in children and youth are due to hemorrhage or ischemic brain infarction. Systemic inflammation is present in DKA, with resultant vascular endothelial perturbation that may result in coagulopathy and increased hemorrhagic risk. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 77 publications
(112 reference statements)
1
75
0
6
Order By: Relevance
“…An examination of 34 adult patients with uncomplicated DKA demonstrated evidence of endothelial injury, platelet activation, relative hypofibrinolysis and activation of the coagulation system, even in the absence of clinical signs of thrombosis. 18 We were unable to demonstrate any clinically significant changes in coagulation during DKA. This is in keeping with a TEG study in children presenting with DKA, which failed to find any clinically significant changes in TEG parameters despite an average pH of 7.04.…”
Section: Discussionmentioning
confidence: 92%
“…An examination of 34 adult patients with uncomplicated DKA demonstrated evidence of endothelial injury, platelet activation, relative hypofibrinolysis and activation of the coagulation system, even in the absence of clinical signs of thrombosis. 18 We were unable to demonstrate any clinically significant changes in coagulation during DKA. This is in keeping with a TEG study in children presenting with DKA, which failed to find any clinically significant changes in TEG parameters despite an average pH of 7.04.…”
Section: Discussionmentioning
confidence: 92%
“…Cerebrovascular disruption increases permeability, allowing fluid to pass into the brain parenchyma, causing vasogenic edema (24). Compromised microvessels are also prone to platelet adhesion and aggregation that could result in hemorrhage or stroke (12,34).…”
Section: Discussionmentioning
confidence: 99%
“…A frequent complication of type-1 diabetes is diabetic ketoacidosis (DKA), a state of severe insulin deficiency resulting in hyperglycemia, ketonemia, and metabolic acidosis (5). Potential consequences of DKA in children include cerebral hemorrhage (32,34), stroke (12,40), and vasogenic edema (11,15,24), suggesting cerebrovascular dysfunction.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the ketones, especially AA, can generate superoxide radicals and induce cytokine and adhesion molecule expression, and that ketonemic diabetics have high levels of oxidative stress compared to those of normoketonemic diabetic patients [13,14,16,20,24,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. We observed that AA was significantly able to upregulate NOX4 expression and NADPH oxidase activity, while BHB failed to produce any adverse effects in HUVEC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand elevated blood ketones are associated with the worsening of hyperglycemia, and patients with ketosis onset T2D showed much more severe insulin resistance compared to nonketotic onset T2D patients [14,15]. Several studies have also shown that diabetes associated ketoacidosis can cause cerebral edema, hemorrhagic stroke, or acute ischemia leading to intracerebral complications [16,17]. Recent studies using MRI measures show altered brain structure and injury associated with adverse neurocognitive outcomes including impairment in neuronal function and viability in T1D children [18,19].…”
Section: Introductionmentioning
confidence: 99%